Response to antiseizure medications in epileptic patients with malformation of cortical development. (October 2021) - Chen, Wei; Jin, Bo; Aung, Thandar; He, Chenmin; Chen, Cong; Wang, Shan; Ding, Yao; Ding, Fang; Wang, Chao; Li, Hong; Jiang, Biao; Zheng, Zhe; et al.
Background: Malformation of cortical development (MCD) is one of the most common causes of pharmacoresistant epilepsy. Improving the knowledge of antiseizure medications (ASMs) treatment response in epileptic patients with MCD is crucial for optimal treatment options, either pharmacological therapy or non-pharmacological intervention. Aim: To investigate the patterns of medical treatment outcome and the predictors for seizure freedom (SF) with ASM regimens in epilepsy caused by MCD. Methods: The epileptic patients with MCD were consecutively enrolled from March 2013 to June 2019. SF was defined as no seizures for at least 12 months or three times the longest pretreatment inter-seizure interval, whichever was longer. Outcomes were classified into three patterns: pattern A: patients achieved SF at one point and remained so throughout follow-up; pattern B: patients' seizures fluctuated between periods of SF and relapse; pattern C: SF never attained. The terminal SF was defined if the patients remained SF at the last follow-up visit. Results: A total of 164 epileptic patients with MCD were included. Pattern A was observed in 22, pattern B in 42, and pattern C in 100 patients. SF was ever achieved in 64 (pattern A and B) patients. Twenty-nine patients had terminal SF after a median follow-up time of 4.3 years. With continuing ASM treatment, seizure relapse risk was very low after a 5-year seizure-free period. The pretreatment seizure frequency was the only independent predictor for pattern A and seizure relapse. Sodium channel blockers monotherapy (33.8%) was more effective than levetiracetam (4.5%) in rendering SF in the initial ASM regimen. Conclusion: Medical treatment can be successful in a minority of epileptic patients with MCD, and pretreatment seizure frequency helps to predict the treatment outcome. An unequal efficacy of ASMs in epilepsy caused by MCD suggests etiological evaluation is vital in the management of focal epilepsy.